Potensi Kader Posyandu sebagai Tenaga Skrining Early Childhood Caries (ECC) Tidak Terawat - Arymbi Pujiastuty (Faculty of Dentistry Universitas Andalas, 2023)
Background: Early Childhood Caries (ECC) is a significant health problem. Untreated ECC can have substantial impacts on individuals and communities, causing pain, disrupting functions, hindering the child's growth process, affecting the child's weight, and influencing the child's developmental progress, ultimately reducing the quality of life for the child. Preventive efforts for untreated ECC include activities such as ECC screening, allowing for prompt intervention in cases of untreated ECC. Non-dental health personnel, such as community health workers, are alternative resources that can be empowered to participate in screening for untreated ECC using pufa Index. Purpose: to analyze the level of validity and reliability of community health workers in conducting screening for untreated ECC using the pufa index. Methods: The research design involves diagnostic testing with a cross-sectional approach, and samples are taken from children in community health posts using simple random sampling. The study is conducted in the working area of the Sijunjung Health Center, Sijunjung District, West Sumatra. Results: The reliability of cumulative PUFA examinations by Community health workers with a Kappa value of 0.88 is considered a very strong level of agreement. The sensitivity and specificity values of cumulative PUFA are 96% and 94%, respectively, which indicate excellent diagnostic values. This means that Community health workers demonstrate a very strong level of agreement and excellent accuracy in diagnosing untreated ECC using the PUFA index in young children. Conclusion: Community health workers have great potential to be empowered as personnel for screening untreated ECC using pufa index.